An inventory of glacial lakes in the South Shetland Islands (Antarctica): temporal variation and environmental patterns - PETSCH,CARINA (2022)
Abstract Monitoring and inventorying proglacial lakes in the Maritime Antarctica region is essential for understanding the effects of climate change on these environments. This study uses Landsat images to create a map of lakes in ice-free areas of the South Shetlands Islands (SSI) for 1986/89, 2000/03 and 2020, and verification of patterns of change in lake areas and numbers. Normalized water difference index (NDWI) products, image segmentation, field records, and cartographic products from other studies were used to validate the results. Results show a 60% increase in the number of lakes from 1986/89 to 2000/03; and a 55% increase from 2000/03 to 2020. There was a 52% increase in lake areas from 1986/89 to 2000/03; a 79% increase from 2000/03 to 2020; and a 173% increase from 1986 to 2020. From 1986 to 2020, the most significant changes were a decrease in the average elevation and distance from glaciers and an increase in distance from the sea. In 2020, SSI lakes were predominantly coastal and ice-marginal, with an E and S orientations, flat surfaces, and a low declivity.